Metabolic demand stimulates CREB signaling in the limbic cortex: implication for the induction of hippocampal synaptic plasticity by intrinsic stimulus for survival - Estrada, Nelly M.; Isokawa, masako (Frontiers in Systems Neuroscience, 2009)
Caloric restriction by fasting has been implicated to facilitate synaptic plasticity and promote contextual learning. However, cellular and molecular mechanisms underlying the effect of fasting on memory consolidation are not completely understood. We hypothesized that fasting-induced enhancement of synaptic plasticity was mediated by the increased signaling mediated by CREB (c-AMP response element binding protein), an important nuclear protein and the transcription factor that is involved in the consolidation of memories in the hippocampus. In the in vivo rat model of 18 h fasting, the expression of phosphorylated CREB (pCREB) was examined using anti-phospho-CREB (Ser133) in cardially-perfused and cryo-sectioned rat brain specimens. When compared with control animals, the hippocampus exhibited up to a two-fold of increase in pCREB expression in fasted animals. The piriform cortex, the entorhinal cortex, and the cortico-amygdala transitional zone also significantly increased immunoreactivities to pCREB. In contrast, the amygdala did not show any change in the magnitude of pCREB expression in response to fasting. The arcuate nucleus in the medial hypothalamus, which was previously reported to up-regulate CREB phosphorylation during fasting of up to 48 h, was also strongly immunoreactive and provided a positive control in the present study. Our findings demonstrate a metabolic demand not only stimulates cAMP-dependent signaling cascades in the hypothalamus, but also signals to various limbic brain regions including the hippocampus by activating the CREB signaling mechanism. The hippocampus is a primary brain structure for learning and memory. It receives hypothalamic and arcuate projections directly from the fornix. The hippocampus is also situated centrally for functional interactions with other limbic cortexes by establishing reciprocal synaptic connections. We suggest that hippocampal neurons and those in the surrounding limbic cortexes are intimately